2021
DOI: 10.1075/ihll.31.06kan
|View full text |Cite
|
Sign up to set email alerts
|

Allowable temporal distances for future-time forms

Abstract: Learners may show sensitivity to linguistic factors in more controlled tasks before doing so in production, although advanced learners often demonstrate greater inter-task consistency. Future-time expression in Spanish serves as a good test case for such variability due to the multiple forms speakers use. Although recent research has considered production and contextualized selection of future-time forms, it has not required learners to react to forms the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Nonetheless, unlike other aspects of Spanish morphosyntax where incomplete acquisition (Montrul 2008) or convergent simplification (Silva-Corvalán 1994) was reported in studies on heritage Spanish, our data on future-time expression mostly showed systematic variation comparable to that reported for monolingual NSs in previous literature. Moreover, for the L2 learners, similar to previous literature, there was (i) an attenuated effect of certainty, modulated by proficiency and tending toward a non-targetlike pattern (Gudmestad andGeeslin 2011, 2013), (ii) an effect for the presence of a temporal adverb (Gudmestad and Geeslin 2011;Kanwit and Solon 2013), and (iii) an effect of temporal distance (Gudmestad and Geeslin 2011;Kanwit 2021;Kanwit and Solon 2013). Our data, thus, indicated that the HLLs had an advantage, as compared to the L2 learners, in the acquisition of future-time expression.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Nonetheless, unlike other aspects of Spanish morphosyntax where incomplete acquisition (Montrul 2008) or convergent simplification (Silva-Corvalán 1994) was reported in studies on heritage Spanish, our data on future-time expression mostly showed systematic variation comparable to that reported for monolingual NSs in previous literature. Moreover, for the L2 learners, similar to previous literature, there was (i) an attenuated effect of certainty, modulated by proficiency and tending toward a non-targetlike pattern (Gudmestad andGeeslin 2011, 2013), (ii) an effect for the presence of a temporal adverb (Gudmestad and Geeslin 2011;Kanwit and Solon 2013), and (iii) an effect of temporal distance (Gudmestad and Geeslin 2011;Kanwit 2021;Kanwit and Solon 2013). Our data, thus, indicated that the HLLs had an advantage, as compared to the L2 learners, in the acquisition of future-time expression.…”
Section: Discussionsupporting
confidence: 84%
“…With respect to temporal distance, previous research seemed to converge on the PF as the form that is not marked for temporal distance, the PI as the close future form, and the MF as the distant future form (Blas Arroyo 2008;Claes and Ortiz López 2011;Díaz-Campos and Escalona Torres 2018;Gudmestad and Geeslin 2011;Kanwit 2021;Kanwit and Solon 2013). For both groups in the current study, the results regarding the PF and PI were similar and reflected the trend previously attested in the literature.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation